2007
DOI: 10.1111/j.1540-8175.2006.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Venous Flow Assessed by Doppler Echocardiography in the Management of Atrial Fibrillation

Abstract: Pulmonary venous blood flow (PVF) visualized by Doppler echocardiography exhibits a pulsatile behavior, which is related to left atrial pressure and function, mitral valve function, and left ventricular compliance. In atrial fibrillation (AF), the disappearance of atrial reverse flow, a decrease in systolic flow with a greater diastolic than systolic flow, a prolonged onset of systolic flow and the appearance of an early systolic reverse flow are characteristic findings. A reduction in systolic PVF expressed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Conversely, Yoshida et al 26 found a good correlation between LAAFV and LA wall contraction velocity. 30,31 However, mitral inflow is thought to be affected by age and hemodynamic loading conditions. Antonielli et al 29 also found that a higher LAAFV was associated with better maintenance of SR after cardiover-sion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Yoshida et al 26 found a good correlation between LAAFV and LA wall contraction velocity. 30,31 However, mitral inflow is thought to be affected by age and hemodynamic loading conditions. Antonielli et al 29 also found that a higher LAAFV was associated with better maintenance of SR after cardiover-sion.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies assessed atrial systolic function using mitral inflow and PV flow. 30,31 However, mitral inflow is thought to be affected by age and hemodynamic loading conditions. 32,33 This study found no difference in the mitral inflow A-wave between patients with and without AF recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Following a short stabilization period, a baseline femoral or testicular arterial blood flow was recorded by the PW Doppler mode during a 50 second cine loop and quantified by analyzing the Velocity-Time Integral (VTI) [15]-[18]. When the PW Doppler mode curve is integrated, it yields a VTI that indicates the distance the blood travels during a certain cardiac circle.…”
Section: Methodsmentioning
confidence: 99%
“…Those patterns of pulmonary venous blood flow changes are related with LA dysfunction, mainly in atrial relaxation, compliance, and reservoir function 15). Assessment of pulmonary venous blood flow variables and patterns by Doppler echocardiography seems useful in the management of AF patients 16). Especially, the reduction in systolic pulmonary venous blood flow may be used as marker for LA dysfunction which favors thrombus formation and AF reinitiation 16)…”
Section: Discussionmentioning
confidence: 99%